How painful can it be? Rheumatic diseases through the eyes of future nurses - Sá, C.; Oliveira, A. (Mediterranean Journal of Social Sciences, 2014)
Rheumatic diseases, by their nature and symptoms are one of the diseases that have the greatest impact on public health, affecting thousands of people, and being directly responsible for serious limitations, not only on a physical level but also the emotional and social level. These diseases have a chronic nature. In many cases, they seriously influence the well-being of many people, as well as their productivity, and regular activity. They are associated with several problems, within the family or at a professional domain, forcing to major changes in the patients' routines, leading to situations of limitation, disability (temporary or permanent), absenteeism, impossibility to accomplish some tasks and duties, or early retirement. Nursing has an essential role on the prevention and management of chronic illnesses, giving healthcare and support to patients, in different stages of their illness. The aim of this study is to understand how students of nursing represent the situation and the problems of the patients affected by rheumatic diseases. We carried out a focus group with twelve students, three men and nine women with a mean age of 20 years, attending the 2nd year of the nursing program. On the interaction with the participants, we focused our attention on three questions: What is a rheumatic disease?; What are the implications of the disease for the person, and in his self-care?; How does rheumatic disease influences the image that a person has of himself? Future nurses consider that rheumatic disease has major consequences in people's lives, in their daily activities, work and family, pointing out that pain and bodily changes contribute to decreased self-esteem, lack of confidence and social isolation.